Substitution saturation and nuclear paralogs of commonly employed phylogenetic markers in the Caryophyllidea, an unusual group of non-segmented tapeworms (Platyhelminthes) - Brabec, Jan; Scholz, Tomáš; Králová-Hromadová, Ivica; Bazsalovicsová, Eva; Olson, Peter D (International journal for parasitology, 2012)
Caryophyllidean cestodes (Platyhelminthes) represent an unusual group of tapeworms lacking serially repeated body parts that potentially diverged from the common ancestor of the Eucestoda prior to the evolution of segmentation. Here we evaluate the utility of two nuclear and two mitochondrial molecular markers (ssrDNA and lsrDNA, nad3 and cox1) for use in circumscribing generic boundaries and estimating interrelationships in the group. We show that these commonly employed markers do not contain sufficient signal to infer well-supported phylogenetic estimates due to substitution saturation. Moreover, we detected multiple trnK+nad3+trnS+trnW+cox1 haplotypes within individuals, indicating a history of gene exchange between the mitochondrial and nuclear genomes. The presence of such nuclear paralogs (i.e. numts), to our knowledge described here in cestodes for the first time, together with the results of phylogenetic, saturation and split-decomposition analyses all suggest that finding informative markers for estimating caryophyllidean evolution is unusually problematic in comparison to other major lineages of tapeworms.
Keywords: Phylogeny; mitochondriální proteiny; proteiny červů; Molecular Sequence Data; Animals; fylogeneze; genetické markery; Cell Nucleus; buněčné jádro; Mitochondrial Proteins; zvířata; Helminth Proteins; molekulární sekvence - údaje; Genetic Markers; Cestoda